DESAIN KELEMBAGAAN PETANI PADI SAWAH MENUJU PENGELOLAAN IRIGASI BERKELANJUTAN DI DESA JATI BALI KECAMATAN RANOMEETO BARAT KABUPATEN KONAWE SELATAN - Yusriadin Yusriadin; Rahayu Endah Purwanti; Normal Bivariant Padangaran; Pertiwi Syarni (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2026)
Classic problems that often culminate in conflicts in the utilization of common-pool resources, including irrigation systems, have led to declining farmer participation in contributing to irrigation infrastructure maintenance. As a consequence, irrigation functionality deteriorates due to damage, which in turn affects water availability for lowland rice production. This study aims to analyze the behavior of water-user farmers in the utilization of irrigation water and to formulate an institutional design for irrigation water management. The research was conducted in Jati Bali Village, West Ranomeeto Sub-District, South Konawe Regency, in October 2025. Data were collected using game experiment and choice experiment approaches, namely social experiments designed to simulate real-world situations faced by the subjects, in this case farmers who are members of Water User Farmer Associations (P3A). The data were analyzed using hierarchical linear regression. The results show that education level, landholding size, proportion of water rights, social trust, the presence of monitoring, and penalty tariffs have a positive and significant effect on the magnitude of individual players’ investment. Meanwhile, age does not have a significant effect. This indicates that the effectiveness of lowland rice irrigation management, both in experimental settings and under real field conditions, is highly dependent on a combination of secure water rights, monitoring and sanction mechanisms, and the level of social trust among farmers.